2011
DOI: 10.1016/j.jaci.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Advances in pediatric asthma in 2010: Addressing the major issues

Abstract: Last year's Advances in Pediatric Asthma concluded with the following statement "If we can close these [remaining] gaps through better communication, improvements in the health care system and new insights into treatment, we will move closer to better methods to intervene early in the course of the disease and induce clinical remission as quickly as possible in most children". This year's summary will focus on recent advances in pediatric asthma that take steps moving forward as reported in Journal of Allergy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 122 publications
0
22
0
2
Order By: Relevance
“…3,4 Despite the effectiveness of ICS intervention, [1][2][3][4] the prevalence of uncontrolled asthma in the pediatric population remains high. 5,6 Fluticasone furoate (FF) is a novel ICS being developed as once-daily monotherapy, and in combination with the novel once-daily long-acting b 2 -agonist (LABA), vilanterol (VI), for the treatment of adult and pediatric (!5 years) asthma. Both FF and VI have demonstrated efficacy and tolerability in adult asthma, 7,8 with once-daily dosing of FF exhibiting similar efficacy to twice-daily dosing.…”
mentioning
confidence: 99%
“…3,4 Despite the effectiveness of ICS intervention, [1][2][3][4] the prevalence of uncontrolled asthma in the pediatric population remains high. 5,6 Fluticasone furoate (FF) is a novel ICS being developed as once-daily monotherapy, and in combination with the novel once-daily long-acting b 2 -agonist (LABA), vilanterol (VI), for the treatment of adult and pediatric (!5 years) asthma. Both FF and VI have demonstrated efficacy and tolerability in adult asthma, 7,8 with once-daily dosing of FF exhibiting similar efficacy to twice-daily dosing.…”
mentioning
confidence: 99%
“…28 Maternal distress has been associated with the development of childhood asthma, so understanding the child's birth history is an important part of the diagnostic process. 44 Dreger and colleagues 45 investigated the association between children's cortisol concentrations and the combined predictors of exposure to maternal distress and childhood asthma. Among children exposed to recurrent maternal stress, Dreger et al found that an increase in cortisol concentrations occurs in response to an acute stressor when there is no diagnosis of asthma; however, children with asthma tend to exhibit lower cortisol concentrations.…”
Section: Other Factors To Consider During History Takingmentioning
confidence: 99%
“…They recommended that increased recognition of even very mild, subclinical asthma symptoms is important. 44,47 Proposed strategies for improving asthma care include the use of standardized screening questionnaires to assess symptoms using the modified Asthma Predictive Index (mAPI) and to predict likelihood using the Asthma Control Questionnaire and the Asthma Control Test. The Asthma Predictive Index (API) was derived from data from the Tucson cohort and developed to help clinicians identify those children who will continue wheezing into older childhood.…”
Section: Other Factors To Consider During History Takingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, despite the proven benefit of written asthma self management plans, currently less than 50 % of Australian children with asthma own one [6]. This may be attributed to the gap that exists between evidence based recommended practice and the current practice of health care professionals in managing paediatric asthma in primary care [5,7,8]. This emphasises the need to facilitate the translation of national guidelines into primary care.…”
Section: Introductionmentioning
confidence: 99%